2017
DOI: 10.1063/1.4989891
|View full text |Cite
|
Sign up to set email alerts
|

Radiation degradation prediction for InGaP solar cells by using appropriate estimation method for displacement threshold energy

Abstract: InGaP solar cells are not predicted to be susceptible to displacement damage by irradiation with electrons at energies lower than 100 keV from non-ionizing energy loss (NIEL) calculations. However, it is recently observed that InGaP solar cells are shown to degrade by irradiation with 60 keV electrons. This degradation is considered to be caused by radiation defects but is not clear. In this study, the kind of the defects generated by electrons at energies lower than 100 keV is found by deep-level transient sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Several quantities in the NIEL formula and, more generally, the overall understanding of radiation damage can be strongly improved via AIMD and TDDFT+MD studies. T d , for example, is an important quantity that can significantly affect the NIEL [185,186] and its accurate estimation can be accessed by AIMD simulations [187,188]. Recent results for T d in semiconductors have shown that the electronic excitations can, in general, reduce their value [122], in line with previous experimental results [189].…”
Section: Improving the Model For Solar Cell Degradation Via A Multisc...supporting
confidence: 69%
“…Several quantities in the NIEL formula and, more generally, the overall understanding of radiation damage can be strongly improved via AIMD and TDDFT+MD studies. T d , for example, is an important quantity that can significantly affect the NIEL [185,186] and its accurate estimation can be accessed by AIMD simulations [187,188]. Recent results for T d in semiconductors have shown that the electronic excitations can, in general, reduce their value [122], in line with previous experimental results [189].…”
Section: Improving the Model For Solar Cell Degradation Via A Multisc...supporting
confidence: 69%
“…5) However, in our previous studies, it was observed that electrons at 60 keV generate radiation-induced defects resulting from the recoil of phosphorus atoms and thus cause the degradation of InGaP solar cells. [6][7][8] This unexpected degradation is probably caused by the incorrect value of displacement threshold energy (E d ) in NIEL.…”
Section: Introductionmentioning
confidence: 99%
“…shown in [36] for the InGaP compound, that to get calculated Fig. 2(a) shows that at low electron energies E e (up to about 314 1 MeV) there is a significant difference between the NIEL c 315 results for different E d values.…”
Section: B Niel C For Gapmentioning
confidence: 90%